Muhammad dan psikologi basyariahnya dalam perspektif agnostik: Sebuah refleksi atas pemikiran Lesley hazleton - Syahrullah, Rahmat Makruf (Maliki Interdisciplinary Journal, 2024)
As a writer, researcher and critic Lesley Hazelton takes an analytical approach to religious narratives, particularly Islam. Lesley Hazleton is best known for her critical approach to religious events, which often includes examining religious narratives without favoring a particular religious perspective. She has also written about the role of psychology in the life of Muhammad and the teachings of Islam. In the book “The Person of Muhammad: The Prophet's Life in History, Politics, Religion, and Psychology", Hanzleton describes Muhammad from a psychological perspective, including Muhammad's behavior that can influence the teachings of Islam. The book “The Person of Muhammad: The Prophet's Life in History, Politics, Religion, and Psychology” by Lesley Hazleton presents a reflection on the teachings of Muhammad, as recorded in Islamic history. From a psychological perspective, Muhammad's teachings can be seen as a system that encompasses various aspects of life. Muhammad created an all-encompassing belief system, which can be seen as a system that organizes life in terms of mental, emotional, social and physical aspects. From a psychological point of view, Muhammad's teachings can be seen as a system that organizes life in terms of mental, emotional, social and physical aspects. However, from an agnostic perspective, Muhammad's teachings can be seen as a belief system that is unreachable by agnostic thinking. Agnostics consider that belief in God cannot be validated or disproved.